Relevansi Belanjawan Negara terhadap Pola Pengundian di Malaysia - Hairol Anuar Mak Din; Rosfazila Abd Rahman; Md Rozalafri Johori; Marzudi Md Yunus (Neolectura, 2022)
-In a parliamentary democratic system, the power of the people through voting is so important in determining the annihilation of the ruling party's life. Meanwhile, junior voters are the largest group of voters and are very sensitive to issues and national policies. The purpose of this study is to explain the relevance of the APBN to voting patterns. The principles of this study use qualitative principles with a study approach. Data were obtained using triangulation by carrying out a literature review of several documents. The object of study submitted is in Malaysia by considering other countries as a comparison. The results of research other than this are the Value Distribution Process Model Approach which is used as the basis for meeting the demands of this objective investigation. The word politics actually refers to the process of social choice. Social also includes all human activities. It generates human processes related to each other, in which the relationship involves power and all individuals in society which will be political. This matter can be seen in several human activities such as voting, showing feelings, paying excise, the right to formal education, human rights, and so on which make these humans directly involved in political processes and activities. Thus, shopping is an element involved in social choice, which is relevant to the lottery pattern in Malaysia. Overall this situation shows that the response among respondents is very satisfactory and this can be justified through the data discussed.